Bacteriophage P1 as a vehicle for Mu mutagenesis of Salmonella typhimurium. - Rosenfeld, S A (1980)
We developed a procedure using bacteriophage P1 as a vector for transferring Mu phage deoxyribonucleic acid into Salmonella typhimurium. Mu phage transferred in this manner yielded lysogenic auxotrophs, and we demonstrated that specific deletions and lac gene fusions can be selected.